Design Improvement of Employee Performance Appraisal Management In PT Bina Kayu Lestari Tasikmalaya - Herlina, Firda; Gustomo, Aurik (Journal of Business and Management, 2015)
Abstract. Performance appraisal is one of the important components in the rational and systematic process of human resources management. The Primary reason for having a performance appraisal program is to monitor employeeâ€™s performance, motivate staff and improve the company morale. In PT Mantu, the monitoring employee performance requires routine is from the attendance there is still use manual attendance, which is accomplished through completing a performance appraisal form which call â€œAmanoâ€. The current performance appraisal system is not have the formal procedure so that the effect for the employees is perceived unfairness of the performance review during the performance appraisal process. This research is done using quantitative and qualitative data to know the employee performance appraisal system in current system and how to improve this system to the future in PT Mantu. The current employee performance appraisal system in PT Mantu cannot increase the employee performance and increase the employee productivity because the company not clearly criteria to appraise the employee performance. Not have the formal procedure to performance appraisal process. Not use the formal performance appraisal form. This research have the recommendation such as: design of performance appraisal, the criteria of employee performance appraisal system is, method of employee performance appraisal and period of employee performance appraisal.Â Keywords: Employee Performance Appraisal, Performance Appraisal